Union use of social media: a study of the University and College Union on Twitter. (November 2015) - Hodder, Andy; Houghton, David
Abstract : The importance of the Internet to trade unionism has not gone unnoticed by academics, and while many have perceived the need for unions to engage in social media, there has not been any study of how unions use social media. This paper provides a systematic examination of union social media use in terms of method, scope and content. The University and College Union (UCU) Twitter account was used as a case study. Tweets ( n  = 1, 615) were collected over a four‐month period (January 1–April 30, 2014) from the official UCU account with followers ( n  = 12, 301) also categorised to determine who is listening. Findings are discussed with reference to earlier debates on union use of the Internet. We find that while UCU has moved with technological developments by using Twitter, the content of the union's messages remain in line with traditional union communication, and the engagement opportunities of social media are underutilised.